Operational analytics as a data monitoring and event management tool of the cyber security management systems - Kachynskyi, A.B.; Stremetska, M.S. (Reports of the National Academy of Sciences of Ukraine, 2021)
With growing demand for the digitalization of data collection, transmission, processing and storage processes in all life spheres of individual, society, and state, there is an urgent need to construct an infrastructure of information transmission networks which can provide a secure connection between endpoints and data centers. These networks must have high availability and provide the fast and efficient processing of information requests, especially in case of critical infrastructure networks. A structural functional scheme of data management for SIEM systems which includes straight and reverse relations between physical, mathematical and analytical levels is proposed, based on the stratum theory by M. Messarovich. A model of multilevel system for the data monito ring and cyber security event management is built in order to provide a systematic approach to maintain the safety state of complex systems and to ensure mechanisms for the operative real-time cyber security incident response.